Mental health in children and adolescents with overweight or obesity - Lucas-Johann Förster; Mandy Vogel; Robert Stein; Anja Hilbert; Julius Lars Breinker; Marleen Böttcher; Wieland Kiess; Tanja Poulain (BMC, 2023)
Abstract Background Overweight and obesity represent huge concerns for children's physical and mental well-being. This study examined the relationship between body mass index (BMI) and health-related quality of life (HRQoL), somatoform complaints, and behavioral problems in children and adolescents. Additionally, the influence of sex, age, and socioeconomic status (SES) on these associations was considered. Methods In total, we studied 2350 participants between the ages of 4 and 18 years (1213 4- to 10-years-old (child sample) and 1137 11-to 18-year-olds (adolescent sample)). To assess HRQoL, somatoform complaints, and behavioral difficulties, we applied the KIDSCREEN-27, a short form of the Giessen Complaints Questionnaire, and the Strengths and Difficulties Questionnaire (SDQ). The BMI was transformed to BMI standard deviation scores (BMI-SDS), according to German gender- and age-specific reference data. Associations were investigated using linear regression analyses. Each association was checked for interaction with sex, age, and SES. Results Regarding HRQoL, we found worsening scores in physical well-being and psychological well-being with increasing BMI-SDS. Somatoform complaints were not significantly associated with BMI-SDS. Conduct problems, peer relationship problems, and emotional problems (the latter only in the adolescent sample) were positively associated with BMI-SDS. While we did not observe any significant interactions with sex, we found some significant interactions with age and/or SES. Conclusion Our findings highlight the importance of mental difficulties in children and adolescents with higher BMI and, consequently, underline the relevance of including psychological interventions in the treatment of overweight or obesity.